2018
DOI: 10.1016/j.yebeh.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

d-Leucine: Evaluation in an epilepsy model

Abstract: d-Leucine treatment was ineffective against chronic seizures after kainic acid-induced status epilepticus, but there was some efficacy during the dark cycle. Because d-leucine is highly concentrated in the pineal gland, these data suggest that d-leucine may be useful as a tool for studying circadian patterns in epilepsy. Deletion of the Tas1R2/R3 receptor protected against seizures in the MES-T test and, therefore, may be a novel target for treating seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…D-Leucine is an understudied amino-acid which until recently had had no known activity in eukaryotic cells [ 19 , 52 , 53 , 54 ]. In spite of this, it has long been known that D-leucine is tightly regulated in the brain by DAAO [ 52 ], and that it is present in food and produced by bacteria [ 52 , 53 ].…”
Section: Neuroactive D-isomers Without Direct Nmda Receptor Interamentioning
confidence: 99%
See 4 more Smart Citations
“…D-Leucine is an understudied amino-acid which until recently had had no known activity in eukaryotic cells [ 19 , 52 , 53 , 54 ]. In spite of this, it has long been known that D-leucine is tightly regulated in the brain by DAAO [ 52 ], and that it is present in food and produced by bacteria [ 52 , 53 ].…”
Section: Neuroactive D-isomers Without Direct Nmda Receptor Interamentioning
confidence: 99%
“…In spite of this, it has long been known that D-leucine is tightly regulated in the brain by DAAO [ 52 ], and that it is present in food and produced by bacteria [ 52 , 53 ]. Recently, it has been found that D-leucine is a potent anti-seizure drug that works against induced seizures but fails to prevent chronic epileptic seizures [ 19 , 122 ]. This seems to be because D-leucine is metabolized too quickly in the brain [ 52 ].…”
Section: Neuroactive D-isomers Without Direct Nmda Receptor Interamentioning
confidence: 99%
See 3 more Smart Citations